2019
DOI: 10.1371/journal.pone.0225608
|View full text |Cite
|
Sign up to set email alerts
|

Differences between individuals with schizophrenia or obsessive-compulsive disorder and healthy controls in social cognition and mindfulness skills: A controlled study

Abstract: The study of social cognition (SC) has emerged as a key domain of mental health, supporting the notion that poorer performance in SC tasks is linked to psychopathology, although most studies have primarily addressed only schizophrenia (SZ). Some recent studies have also shown deficits of SC in obsessive-compulsive disorder (OCD) patients; however, little is known about how individuals with OCD may differ on SC performance from individuals with SZ. Moreover, initial research in this field suggests that mindfuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…The shared changes in brain function in SZ and OCD were consistent with the overlapping cognition deficits. SZ and OCD patients presented with homologous impaired cognition in memory, executive function, goal-directed behavior, response inhibition, source monitoring and social cognition ( 3 7 , 32 ). The DLPFC is crucial for working memory and episodic memory processes ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shared changes in brain function in SZ and OCD were consistent with the overlapping cognition deficits. SZ and OCD patients presented with homologous impaired cognition in memory, executive function, goal-directed behavior, response inhibition, source monitoring and social cognition ( 3 7 , 32 ). The DLPFC is crucial for working memory and episodic memory processes ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In OCD patients, obsessions trigger compulsions and avoidances aimed at neutralizing worries. In addition, SZ and OCD both show cognitive impairment in many domains, including memory, executive function, goal-directed behavior, response inhibition, source-monitoring and social cognition, and SZ has greater deficits than OCD ( 1 , 3 7 ). Furthermore, there are increasing epidemiological studies showing the relationships between the two disorders.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of basic research on dispositional mindfulness in schizophrenia ( Martins et al, 2017 ), despite the increasing use of mindfulness-based interventions for treating people with psychotic disorders (meta-analysis by Jansen et al, 2020 ). A foundational study by Tabak et al (2015) found that people with schizophrenia reported lower levels of self-reported mindfulness relative to unaffected comparison participants (although others did not observe these group differences; López-Del-Hoyo et al, 2019 ). Less dispositional mindfulness correlates with worse overall symptom severity in people with schizophrenia ( Hochheiser et al, 2020 ), including greater clinician-rated amotivation ( Lee and Yu, 2021 ).…”
Section: Psychological Dimensions Relevant To Amotivation and Anhedoniamentioning
confidence: 99%
“…López-Del-Hoyo et al (2019) compared schizophrenia and OCD patients on social cognitive measures, the results showed significant differences only for attributional style (intentionality bias and anger bias) with higher scores in the OCD group. 45 In respect to self-serving bias, in another study, OCD patient did not differ from healthy controls and paranoid or non-paranoid clinical groups; OCD patients also made comparable degree of internal attribution for both positive and negative outcomes with other groups. 47 A meta-analysis 36 indicates that cognitive vulnerabilities which were developed in the context of depression may not be unique to depression, rather high comorbidity and lack of symptom specificity between anxiety and depression indicates involvement of these vulnerabilities in anxiety disorders as well.…”
Section: Other Attribution Stylesmentioning
confidence: 92%
“…Fourteen (73.68%) of the studies [42][43][44][45][46][47][48][49][50][51][52][53][54][55] were cross-sectional, four (21.05%) studies [56][57][58][59] were therapeutic interventions and one study 35 (5.26%) was meta-analysis in nature. Range of sample size for cross-sectional studies was 41-214 and for intervention was 24…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%